2020
DOI: 10.3390/cryst10060477
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Chemistry of the [Cu(4,7-Dichloroquinoline)2Br2]2 Dimeric Complex through Structural Analysis: A Borderline Ligand Field Case

Abstract: Large dark prismatic crystals (P 1 ¯ ) consisting of closely packed centrosymmetric [Cu(4,7-dichloroquinoline)2]2Br4 binuclear units are formed when 4,7-dichloroquinoline (DCQ, C9H5NCl2) binds copper(II). Cu2+ adopts a strongly distorted square pyramidal coordination geometry, perturbed by electrostatic interactions with two axial μ–Br ligands acting as highly asymmetric bridges. It is shown that, as electronic states of ligands are higher in energy than the metal ones, antibonding orbitals bear signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…When theoretical EDDs are compared to experimental results, it is often said, correctly, that the former are mostly affected by the choice of quantum mechanical method, the latter by quality of the sample, treatment of the data, and choice of multipolar model (to cite only a few sources of error). In all our EDD studies so far (starting with the one of crystalline citrinin at 19 K) [44], we have found that reliable modelling of H atoms requires anisotropic displacement parameters (ADPs), and poles up to the quadrupole level [45,46].…”
Section: The Electron Density Distribution (Edd)mentioning
confidence: 99%
“…When theoretical EDDs are compared to experimental results, it is often said, correctly, that the former are mostly affected by the choice of quantum mechanical method, the latter by quality of the sample, treatment of the data, and choice of multipolar model (to cite only a few sources of error). In all our EDD studies so far (starting with the one of crystalline citrinin at 19 K) [44], we have found that reliable modelling of H atoms requires anisotropic displacement parameters (ADPs), and poles up to the quadrupole level [45,46].…”
Section: The Electron Density Distribution (Edd)mentioning
confidence: 99%
“…X-ray crystallography has given for half a century a fundamental contribution to the quantitative understanding of molecular recognition and crystal packing. For all its merits, it does however provide only a space–time average picture, a limitation that obscures entropic and vibrational effects on cohesive energies. Dynamic information from standard X-ray diffraction experiments is confined to atomic displacement parameters (ADPs), whose interpretation is not always immediate in terms of fundamental physics. , Accounting for dynamic effects is obviously desirable in principle and also for cutting-edge applications like, for example, energy transduction and shape-changing materials . Moreover, thermal expansion coefficient and isothermal compressibility rely on a dynamic interplay among intermolecular interaction forces, often comprehensively dubbed noncovalent interactions (NCIs).…”
Section: Introductionmentioning
confidence: 99%
“…As for the anharmonicity of thermal motion, the relevance of its inclusion in ADP models when analyzing EDDs in crystals is still an open question, the uncertainty being partly related to the fact that very asphericity in atomic charge densities can be due to genuine anharmonic thermal motion and/or to chemical bonding [ 19 ], as well as to static or dynamic disorder [ 20 , 21 ]. Long ago, at an international symposium on the accuracy in structure factor measurement, Werner F. Kuhs presented [ 22 ] a review on the properties of the most widely used formalisms to describe anharmonicity in crystallographic structure analysis and later published a paper [ 23 ] on both the theoretical and experimental aspects of generalized ADPs.…”
Section: Introductionmentioning
confidence: 99%